Multa multat (Pl. Rud. 20) - Dzukeska, Elena (Здружение на класични филолози АНТИКА, 2018)
The present article focuses on the 20-th verse of the prologue of Plautus' Rudens and in particular on the phrase multa multat. This obvious figura etymologica is analyzed as a more complex wordplay based on the double meaning of the word multa, as a form of the Latin word for "fine" and as a form of the adjective multus, "many, much". The semantic relations with the other words in the immediate context are also discussed, as well as the possible etymological connection between multa, "fine" and multus, "many, much". It is concluded that Plautus' play on the words multa, multō and multus is valuable not only as an early literary attestation of the word for "fine", but also as a possible evidence for its etymology.
Keywords: multa, multo, multus, Plautus, wordplay